A Comparative Study of Digital Transformation in HR in the Healthcare Industry: India v/s Dubai (UAE) - Rajiv J. Nair; Dr. Shilpa Kanthalia (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The present paper compares the ways in which digital transformation is changing human resources (HR) in the healthcare industries in Dubai, United Arab Emirates, and India. The paper maps policy drivers, HR digital tools and platforms, workforce up skilling initiatives, significant impediments, and organizational outcomes in each setting using a literature-based comparative method (policy papers, peer-reviewed studies, government announcements, and industry reports in this case). While Dubai exhibits quick, government-driven, centralized digital initiatives with a heavy emphasis on artificial intelligence, up skilling, and institutional preparation, India’s transformation is marked by extensive national interoperability efforts and inconsistent adoption among public and commercial providers. The report ends with actionable suggestions for legislators and HR directors in the healthcare industry to hasten the digitalization of HR in a fair, safe, and people-centered manner.